Fluoride adsorption by doped and un-doped magnetic ferrites CuCexFe2-xO4: Preparation, characterization, optimization and modeling for effectual remediation technologies - Rehman, M.A.; Yusoff, I.; Alias, Y. (Elsevier, 2015)
A series of doped and un-doped magnetic adsorbents CuCexFe2-xO4 (x=0.0-0.5) for fluoride were prepared with the micro-emulsion method. Fluoride adsorption was optimized for solution pH, temperature, contact time, and initial concentration and was monitored via normal phase ion chromatography (IC). The effect of concomitant anions was also explored to perform and simulate competitive fluoride adsorption in real water samples. Optimal adsorption was discovered by a simple quadratic model based on central composite design (CCD) and the response surface method (RSM). The adsorption, electrochemical and magnetic properties were compared between doped and un-doped ferrites. Doped ferrites (x = 0.1-0.5) were found to be superior to un-doped ferrites (x = 0) regarding the active sites, functional groups and fluoride adsorption. The characterization, optimization and application results of the doped ferrites indicated enhanced fluoride adsorption and easy separation with a simple magnet. (C) 2015 Elsevier BM. All rights reserved.